Mediation Tactics for Resolving Conflicts in Trade Unions: A Quantitative Case Study of the Nigeria National Petroleum Corporation, Port Harcourt, Rivers State, Nigeria - Akpan , Hannah; Akpan (MTECH), Imoh Ekpenyong; Olsson , Imaobong (Journal of Social Science Studies, 2023)
Conflict is an inherent part of labor-management relations and has significant implications for organizations. To manage and resolve conflicts effectively, various mediation tactics have been developed to minimize costs, satisfy interests, build relationships, and control resource expenditures. This research aims to explore the utilization and effectiveness of mediation tactics in resolving conflicts within the Nigeria National Petroleum Corporation's (NNPC) Research and Development Department in Port Harcourt, River State, Nigeria. The study examines the causes of organizational conflict and investigates the role of mediation in public enterprises. Data were collected using a self-made questionnaire distributed to 100 respondents in the Research and Development Department. The questionnaire employed a five-point Likert scale to measure opinions and perceptions. The research utilized a descriptive approach, and data analysis involved non-parametric statistics, such as frequency distributions and percentage values. The findings indicate that industrial conflicts frequently arise between employers and employees in the Research and Development Department. However, the study reveals that these conflicts can be effectively managed through mediation with the involvement of the workers' representative trade union. Therefore, the research highlights the importance of regular review of labor agreements and encourages effective employer-employee consultation and negotiation to reduce conflicts, promote industrial harmony, and enhance productivity. This study emphasizes the significance of mediation tactics in resolving conflicts within trade unions. It provides insights into the specific context of the NNPC's Research and Development Department and offers recommendations for organizations and stakeholders in industrial relations to foster conflict resolution, industrial harmony, and increased productivity.